POST-COVID ASIA : Deglobalization, Fourth Industrial Revolution, and Sustainable Development - Yi, Hyon-hun, 1959-; Park, Donghyun (Singapore ; Hackensack, NJ : World Scientific, 2021)
"Coronavirus disease (COVID-19) has been an unprecedented, once-in-a-century gamechanger for the world. The central focus of Post-COVID Asia is the new world that will emerge after the coronavirus. In particular, this book explores how deglobalization will proceed in the post-COVID world and what kind of impact deglobalization will have on Asian economies. After all, in the last few decades, Asia has leveraged globalization to become the world's fastest-growing, most dynamic region. Therefore, an urgent challenge facing Asian economies is to figure out how to survive and thrive when the globalization which served them so well is giving way to deglobalization. Opportunities have emerged for Asian economies amid the winding down of the third wave of globalization. In fact, the next wave of globalization is already beginning to take shape, in tandem with the Fourth Industrial Revolution, which is full of exciting new technologies. This book offers insights that would help governments, companies and people in Asia to ride the next wave of globalization to power their prosperity"--Provided by publisher.
Includes index
Keywords: COVID-19 (Disease) -- Economic aspects -- Asia; Asia -- Economic conditions -- 21st century; Asia -- Economic policy -- 21st century